CONDITION AND SPATIAL DISTRIBUTION OF STONY CORAL IN BUNGURAN, SOUTHWEST NATUNA ISLANDS, INDONESIA - Tuti H., M. I. Yosephine (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 2012)
Bunguran waters is part of Natuna waters consisting of several small islands located in the southern part of South China Sea, between Sumatera and Kalimantan Island. This paper reported results of a study on spatial distribution and condition of coral reefs and other biota in Bunguran waters,i.e. percentage cover and diversity of coral species. The observation was conducted using line intercept transect (LIT) on eight stations distributed in Salor Island, Sedanau Island, Komang Island, Kumbik Island, Depeh Strait, Sabangmawang Island, Pulau Tiga Village and Tekolampak Cape. The results showed that the reef type of Bunguran were mostly fringing reef dominated by Porites cylindrica, P. lutea and P. rus. Porites spp. were evenly distributed in all location observed. A total of 115 coral species belonging to 16 genera were found and the percentage of living coral cover ranged from 43.20 to 63.53 %. Coral cover reached their maximum at 10Ã¢â¬â15 meter depth and decreased rapidly coincident with the increasing depth. In general, the condition of coral cover was in Ã¢â¬ÅgoodÃ¢â¬Â category with the average percentage living cover of coral was estimated 51.38%.